Student's personality and his traits under modern technology in the Kingdom of Saudi Arabia - Altarshi, Bader Thani (Journal of Educational and Psychological Sciences, 2022)
this research, aimed at reading the most important skills that student must have to keep pace with modern digital technology, and use them in his scientific and practical achievement. It has become clear during Corona pandemic that students lack many of these skills. It is hoped that this research will help them to better deal with modern applications. To answer the main question of the research: What are the traits that student must have in order to adapt to modern technology? It required following the deductive inductive approach: following studies, researches and books that talked about the subject and analyzing it, and deducing the most important features and skills required. Finally, the research classified skills into four:1- personal traits Include * Management, organization, direction and effectiveness * Leadership, initiative and strength of character * Motivation and motivation * Flexibility and adaptability *independence *Self-understanding and appreciation (self-confidence) *self-evaluation *emotional smartness.2- Cognitive and digital traits, including * knowledge building (self-learning) * planning and setting goals * programming and analysis for the use of technology * access to information, analyzing it, linking it to each other and applying it in new situations * updating the knowledge content (lifelong learning) * knowledge management.3- Social traits: relationship building, leadership by influence, teamwork, collaborative learning, oral and written communication, interaction and good listening, negotiation and persuasion, knowledge transfer and community digital literacy, global citizenship, and a developmental mindset.4- Creative traits represented in: * Meditation, curiosity, and science fiction * Problem solving * Creativity * Critical reading * Critical thinking * Scientific research skills. It also recommended the following: 1- Conducting a survey research for the students of the College of the Prophet's Mosque to ensure that the students are familiar with the previous skills, 2- Re-designing the curricula to include these features, and including them within the teaching plans.
Keywords: Personal; Student; Traits; Technology